Prevalence, Serotype Diversity, Genotype and Antibiotic Resistance of Listeria monocytogenes Isolated from Carcasses and Human in Korea - Oh, Hyemin (Korean J Food Sci Anim Resour, 2018)
This study investigated the prevalence of Listeria monocytogenes in slaughterhouses, and determined serovars and genotypes, and antibiotic resistance of the isolates obtained from slaughterhouses and humans in Korea. Two hundred ninety samples were collected from feces (n=136), carcasses [n=140 (cattle: n=61, swine: n=79)], and washing water (n=14) in nine slaughterhouses. Eleven human isolates were obtained from hospitals and the Korea Center for Disease Control and Prevention. Listeria monocytogenes was enriched and identified, using polymerase chain reaction (PCR) and 16S rRNA sequencing. Serovars and presence of virulence genes were determined, and genetic correlations among the isolates were evaluated by the restriction digest patterns of AscI. Antibiotic resistance of L. monocytogenes isolates were examined against 12 different antibiotics. Of 290 slaughterhouse samples, 15 (5.17%) carcass samples were L. monocytogenes positive. Most L. monocytogenes isolates possessed all the virulence genes, while polymorphisms in the actA gene were found between carcass and human isolates. Serovars 1/2a (33.3%) and 1/2b (46.7%) were the most frequent in carcass isolates. Genetic correlations among the isolates from carcass and clinical isolates were grouped within serotypes, but there were low geographical correlations. Most L. monocytogenes isolates were antibiotic resistant, and some strains showed resistance to more than four antibiotics. These results indicate that L. monocytogenes are isolated from carcass and human in Korea, and they showed high risk serotypes and antibiotic resistance. Therefore, intensive attentions are necessary to be aware for the risk of L. monocytogenes in Korea.